Understanding informality - Ceyhun Elgin; M. Ayhan Kose; Franziska Ohnsorge; Shu Yu (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
This paper introduces a comprehensive database of informal economic activity. The database focuses on measures that have strong cross-country and over time coverage: it includes both model-based and survey-based measures of informality and covers more than 160 economies for the period 1990-2018. The paper illustrates two applications of the database. First, it distills stylized facts of informal activity, including its declining trend and pervasiveness in emerging market and developing economies (EMDEs). Second, it documents the cyclical features of the informal economy. Overall, informal economy recessions (recoveries) do not differ significantly from those of formal economy. Like formal-economy business cycles, informal-economy business cycles tend to be shallower in advanced economies than in EMDEs. Informal employment in both advanced economies and EMDEs appears to be largely acyclical
Keywords: E26; E32; J46; O17; 330; Informal economy; self-employment; employment; output; business cycles